2021
DOI: 10.3390/ma14205992
|View full text |Cite
|
Sign up to set email alerts
|

Large Deflection Analysis of Peripherally Fixed Circular Membranes Subjected to Liquid Weight Loading: A Refined Design Theory of Membrane Deflection-Based Rain Gauges

Abstract: The anticipated use of elastic membranes for deflection-based rain gauges has provided an impetus for this paper to revisit the large deflection problem of a peripherally fixed circular membrane subjected to liquid weight loading, a statics problem when the fluid–structure interaction of membrane and liquid reaches static equilibrium. The closed-form solution of this statics problem of fluid–structure interaction is necessary for the design of such membrane deflection-based rain gauges, while the existing clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Such a fluid-solid coupling problem presents serious analytical difficulties, which involves the analytical solution to differential-integral governing equations. The mathematical theory for designing such rain gauges, which is presented in our previous study [13], is observed to be inaccurate. It is suitable only for the design of nonlinear (rather than linear) rain gauges, because the ranges of the nearly-linear (seemingly following a linear-dependent relationship) segments in the nonlinear input-output relationships of the rain gauges, which it can provide, are too small or too narrow.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Such a fluid-solid coupling problem presents serious analytical difficulties, which involves the analytical solution to differential-integral governing equations. The mathematical theory for designing such rain gauges, which is presented in our previous study [13], is observed to be inaccurate. It is suitable only for the design of nonlinear (rather than linear) rain gauges, because the ranges of the nearly-linear (seemingly following a linear-dependent relationship) segments in the nonlinear input-output relationships of the rain gauges, which it can provide, are too small or too narrow.…”
Section: Introductionmentioning
confidence: 97%
“…Many thin films are able to exhibit large elastic deflections when subjected to external loads [1][2][3][4][5][6], which makes it possible to develop devices or instruments based on film deflection [7][8][9][10][11][12]. In our previous study [13], to overcome the shortcomings of the existing rain gauges, a new type of membrane deflection-based rain gauge was proposed, which involves a liquid-structure interaction of a peripherally fixed circular membrane under liquid weight loading. Such a fluid-solid coupling problem presents serious analytical difficulties, which involves the analytical solution to differential-integral governing equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "membrane" is a term in mechanics which refers to a laterally loaded thin plate whose edge displacement is always completely constrained (fixed) during deflection. Therefore, "thin plate bending problems" [1-5] differ from "membrane deflecting problems" [6][7][8][9][10], mainly in that the thin plates under lateral loading undergo both tensile stress and compressive stress in bending problems (i.e., undergoing the so-called bending stresses), and undergo only tensile stress in deflecting problems due to the always fully fixed edge displacements (as if the bending stiffness of the plates vanishes). In general, the large deflection problems of laterally loaded thin plates or membranes are solved analytically by establishing the governing equations such as geometric equations and equilibrium equations, in which the accuracies of these governing equations depend usually on whether the deflection effect is properly taken into account, which further affects the accuracies of the solutions of these large deflection problems.…”
Section: Introductionmentioning
confidence: 99%
“…Essential to these technical applications is the ability to solve these problems of a large deflection of the membranes under lateral loading analytically and accurately. However, these large deflections often give rise to strong geometric nonlinearity, and these nonlinear differential equations often present analytical difficulties [22][23][24]. In the existing literature, annular membrane problems are less in evidence in comparison with circular membrane problems [25][26][27][28][29], but are often more difficult to deal with analytically due to the boundary conditions at the inner and outer edges which need to be satisfied simultaneously [30][31][32].…”
Section: Introductionmentioning
confidence: 99%